Performance in Jabatan Kastam Diraja Malaysia, Kedah / Muhammad Zarif Jasni - Jasni, Muhammad Zarif (2017)
Internal control is the integration of the activities, plans, attitudes, policies, and efforts of the people of an organization working together to provide reasonable assurance that the organization will achieve its objective and mission. Therefore this study will focus detail on the relationship between employee motivation, working environment, training & development toward organizational performance. In order to obtain more information, distributing questionnaires are among the method used. This study is organized to identify the factors of organization performance. Furthermore it also will discuss the impact of the internal controls to the Jabatan Kastam Diraja Malaysia, Kedah. The result can be used to ensure the organizations achieve its objectives and also can help the operation run effectively and efficiently.